2015
DOI: 10.4103/0974-9233.150635
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of astigmatism in a population of Tunisian school-children

Abstract: Purpose:To evaluate the characteristics of astigmatism in a cross-sectional study of schoolchildren in Tunisia.Materials and Methods:A random cluster design was used to recruit children from primary schools across urban and rural settings in Tunisia, from 2008 to 2010. A total of 6192 students aged 6–14-years old were enrolled. All students whose uncorrected visual acuity was worse than 20/20 underwent a complete ophthalmic examination. Astigmatism was defined as the cylinder power of 0.75 diopter (D) or great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…Chan et al [4] reported that 32.9% of Taiwanese schoolchildren had astigmatism >1.0 D, a prevalence higher than that of our study. We did not detect correlations with either gender or age like those reported by Chebil et al [22] and Fotouhi et al [9]. Our results also agreed with others [4, 23, 24], where most schoolchildren had WTR astigmatism.…”
Section: Discussionsupporting
confidence: 90%
“…Chan et al [4] reported that 32.9% of Taiwanese schoolchildren had astigmatism >1.0 D, a prevalence higher than that of our study. We did not detect correlations with either gender or age like those reported by Chebil et al [22] and Fotouhi et al [9]. Our results also agreed with others [4, 23, 24], where most schoolchildren had WTR astigmatism.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of astigmatism in this study (38.4%) is similar to the values reported in southern Taiwan (32.9%) [ 22 ], Hangzhou (32.7%) [ 23 ], and Shandong (36.6%) [ 13 ], but significantly higher than those in multiethnic countries (Asian children (8.29%), European children (18.1%), non-Hispanic white children (6.33%), and Tunisian children (6.67%) [ 24 26 ]), which suggests that the prevalence of astigmatism in children and teenagers may be related to racial differences. As early as 2007, some scholars explained it from the perspective of genes [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…In this investigation the prevalence of astigmatism was 6.67% and increased statistically significantly with age ( P = 0.032), but was not significantly related to gender ( P = 0.051). In our investigation we found similar results; the prevalence of astigmatism was 25.5%, astigmatism increased with older age and was not associated with gender ( 43 ).…”
Section: Discussionsupporting
confidence: 85%